DAMPAK MONEY LAUNDERING DI DUNIA PERBANKAN TERHADAP PEREKONOMIAN DI INDONESIA - ACHMAD AFANDI, ZANUAR Achmad (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this study is to know the impacts of money laundering on Indonesianeconomy, and to know the government efforts to prevent it. This study used descriptivemethods with qualitative data analysis. Money laundering not only could decrease thenational income, but also could decrease Indonesia’s reputation. To prevent it happened inIndonesia, bank must obey the Know Your Customer Principles. Besides, bank must obey theregulation of money laundering from Indonesian government. Keywords: Money Laundering, Bank, Know Your Customer Principles